Zusters in islam: Religieuze socialiteit onder Nederlandse bekeerlingen - Vroon-Najem, Vanessa (Religie & Samenleving, 2014)
Most people – Muslims and non-Muslims alike – expect women in the Netherlands to convert to Islam because of marriage. In reality, marriage does not play a pivotal role and there are single women who decide to become Muslim, too (Van Nieuwkerk 2006; Vroon-Najem 2014). This circumstance raises the question how converted women become part of local Muslim communities. As became evident in my research, increasingly, converts have initiated Dutch language women’s groups to help themselves and others to learn how to practice Islam and how to be a (converted) Muslim in the Netherlands. Often, within these groups, women make extensive use of the concept of Islamic sisterhood. To elaborate on this finding, in this article, I will examine the following question: What is the role of the concept of Islamic sisterhood in the context of conversion to Islam in the Netherlands?